2020
DOI: 10.47262/sl/8.3.132020015
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Time and age Links Parasitism, Emergence and Development of Pupal Parasitoid Dirhinus giffardii Against Bactrocera zonata

Abstract: The parasitism, emergence and development of pupal parasitoid, Dirhinus giffardii (Silvestri) was assessed against the pupae of the fruit fly, Bactrocera zonata (Saunders), under laboratory conditions. The fruit fly and D. giffardii were reared in glass cages on the artificial diet, and a known number of different 1-hour (fresh), 1-day, 2-day, 3-day and 4-day old pupae were offered to the respective parasitoids for a period of 6, 12, 18 and 24 hours. It was noted that the parasitism was increased gradually wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…These observations are in accordance with a study which showed that by increasing exposure time and pupal age of peach fruit fly gradually increased the parasitism. Hence, supporting our findings, maximum parasitism was in three days old pupae, also indicating a positive correlation of increasing age with oviposition, development, emergence and parasitism of parasitoid pupa (Awais et al, 2020a).…”
Section: Correlation Between Percent Of B Dorsalis Pupae Parasitized ...supporting
confidence: 91%
“…These observations are in accordance with a study which showed that by increasing exposure time and pupal age of peach fruit fly gradually increased the parasitism. Hence, supporting our findings, maximum parasitism was in three days old pupae, also indicating a positive correlation of increasing age with oviposition, development, emergence and parasitism of parasitoid pupa (Awais et al, 2020a).…”
Section: Correlation Between Percent Of B Dorsalis Pupae Parasitized ...supporting
confidence: 91%
“…To avoid this, many management techniques were used in the past. These include cultural control (Reddy et al, 2020), Mechanical control (bagging) (Karar et al, 2019), physical control (Soto-Reyes et al, 2018; Hasan et al, 2020), Behavioral control (Khan et al, 2020), food baiting techniques (Nisar et al, 2020), Male annihilation techniques (Khan and Naveed, 2017), sterile insect techniques (Sarwar, 2018), biological control (Awais et al, 2020), use of plant extracts (Saddam et al, 2019), use of synthetic insecticides (Khan et al, 2018), Use of Nanoparticles (Farooq et al, 2019) and use of entomopathogenic fungi (Shahzad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%